A educação musical e a promoção da pessoa : estudo de caso em uma obra social - Corusse, Mateus Vinicius (2016)
The musical education developed in the context of social projects has some specifics. Between them is the prospect that, along with the musical development, be done a contribution in human and social development of individuals. Thus, this research develops an investigation of human development carried out from the educational processes of music in a social project in the state of São Paulo. The compreention of human and his promotion was given by personalist philosophy, expressed especially in Karol Wojtyla. The research has a qualitative approach of a case study. Data collection instruments were observations with registration in field diaries and interviews with individuals in social work. Data analysis was given by content analysis. From reading and analyzing the data were found three analytical focuses: understanding of music and music education; understanding and evaluation of the educational process; and understanding and evaluation of human development. Through them it was possible to understand the significance attributed to the file by the members of the social project as well as the dynamics of its operation. Aspects such as the arrangement of musical and human development goals proved to be important, so that could be conceived the concept of redemptive vision of human development. Other important elements were the understanding of performance and presentations as a means of visibility of the institution and family integration and the need for articulation of essentialist and contextualists aspects of music education. Finally, also stands out the need for appropriate training for professionals who work in this place. By the experiences studied in this context, it was found that the musical development was suppressed in view of the proposal for a human development, which ended up compromising both.Consequently there was only a few non-articulated elements favoring a possible human and social action, which in view of the weak configurations of the educational process have not been explored in order to enhance their formative action.